Factors related to the quality of performance of volunteer health worker trainees in Cervantes, Ilocos Sur and Buguias, Benguet - Bumanglag, Julieta Rocio V. (1997)
This study aimed to determine the factors related to the quality of performance of volunteer health worker (VHW) trainees of Cervantes, Ilocos Sur and Buguias, Benguet. Specifically, it also aimed to identify the correlation between the VHW trainees' quality of performance and the following factors: demographic data, educational attainment and socio-economic status. The researcher hypothesized that there is no significant relationship found between the VHW trainees' quality of performance and the above variables. This is a descriptive study conducted at 2 former stations of Medical Ambassadors Philippines (MAP). Instruments used in gathering data include a self-administered questionnaire translated in the Ilocano dialect; performance checklists and rating scales to assess their psychomotor skills and written examinations for each topic to assess their cognitive skills. The survey questionnaire was developed by the researcher and a fellow nurse with the help of literature review and sample questionnaires which MAP used in the conduct of Community Health surveys in the different tribal communities in Luzon and Mindanao. To further establish its validity, experts' view were sought. Meanwhile, performance rating scales and checklists were developed by the researcher based also on literature review while some, particularly those of the Prenatal checklist was adopted from MAP's BHW training manual. Respondents included 82% of the VHW's previously trained by MAP. There were 30 respondents all in all and three out of them volunteered to take part in this study. They were included on the basis of their willingness and availability to participate. Cervantes, Ilocos Sur and Buguias, Benguet were the sites for this study. They were MAP's former mountainous and tribal stations with webs of health problems. Data were summarized using measures of central tendency and frequency distributions. Pearson r Test of correlation was used to analyze quantitative data. Chi Square (X2) Test of Association was used to analyze qualitative data. The level of significance used was 0.05% as a point of reference for the acceptance or rejection of the null hypothesis (Ho). Particularly p>.05 was used as the critical area for the Chi square test of association while ±0.30645 was used as the critical area for the Pearson r test of Correlation. Data were encoded and analyzed using two programs, the EPI-INFO Program and the Microsta Program. Subjecting the data to Chi Square (X2) Test and Pearson r test, the following results emerged: There was no significant difference found between the VHW trainees' quality of performance and the following factors: age, civil status, socio-civic involvement, formal education, other training received, and these VHW trainees' income level. VHW trainees perform well regardless of their background on the above factors. Thus, they are not a prerequisite or criteria in the selection of VHW trainees. Meanwhile the study also revealed that there exists a significant difference between the literacy level and their performance on Wound Care and Suturing (Cognitive) particularly because of the need to justify or rationalize the steps involved in doing the procedure for the client's safety; Family involvement on the Prenatal Care (Psychomotor); Length of residency on Drug Computation (Psychomotor) and Socio-economic status (SES) on Wound Care and Suturing (Cognitive). The SES of the VHW trainee based on this study revealed that it has an inverse relationship with the trainee's performance on Wound Care and Suturing (Cognitive). Meaning, the poorer is your SES, the better is your performance. Endorsement of the VHW trainees by any barangay or municipal official has significant difference on three tests namely: Prenatal Care (Psychomotor), Wound Care and Suturing (Psychomotor-A) and Drug Computation (Cognitive). By nature, the trainee should have some degree of confidence to allow a satisfactory or good performance which can be gained from the teacher or any barangay or municipal officials. With the above findings, the researcher offers the following recommendations. For training agencies implementing VHW training, selection criteria such as the following be included: Literacy level, presence of involvement of any family member in the local government, socio-economic status, and presence of endorsement from any barangay or municipal official to join the training. For the community people and barangay officials who recommends and the VHW trainee-aspirants, the above selection criteria should be considered. This study is open for any replication perhaps in another setting, communities in the urban area and on a different group, respondents who do not have any previous related training. It is also suggested that other variables such as attitude, religion, culture, commitment to work, and presence of salary or remuneration be correlated to the quality of performance of the VHW trainees. Likewise, it is suggested that the sample size be increased and male respondents be included. Aside from this, it can also serve as a reference material for further or related studies.
Special project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Volunteer workers in medical care